Current view on biomedical applications of synthetic metal-polymer nanocomposites - Kaushik, R; Sharma, NK (Janaki Medical College Journal of Medical Science, 2014)
Recent advances in the field of nanotechnology led several groups to recognize the promise of recruiting nanocomposities to the ongoing battle against pathogenic gram-positive and gram-negative bacteria and metal-polymer nanocomposites are a typical example. On the basis of recent literature, the nanocomposities are synthesized mainly by two techniques i.e. in-situ and ex-situ technique and these nanocomposities have great biomedical applications in terms of their antibacterial activity. A large battery of newly developed and discovered nanocomposities has been accumulating during the last decade. DOI: http://dx.doi.org/10.3126/jmcjms.v2i1.11422   Janaki Medical College Journal of Medical Sciences (2014) Vol. 2 (1):52-58